In rats with estradiol valerate-induced polycystic ovary syndrome, the acute blockade of ovarian β-adrenoreceptors improve ovulation - Berenice Venegas; Lizzbeth Yureli De León Gordillo; Gabriela Rosas; Julieta A. Espinoza; Carolina Morán; Roberto Domínguez; Leticia Morales-Ledesma (BMC, 2019)
Abstract Background Polycystic ovary syndrome is characterized by hyperactivity of the ovarian sympathetic nervous system, increases in the content and release of norepinephrine, as well as decreases in the number of β-adrenoreceptors. In the present study, β-adrenoreceptors in the ovaries of rats with polycystic ovary syndrome were blocked and analyzed the resultant effects on ovulation, hormone secretion and the enzymes responsible for the synthesis of catecholamines. Methods At 60 days of age, vehicle or estradiol valerate-treated rats were injected with propranolol [10− 4 M] into the ovarian bursas on oestrus day. The animals were sacrificed on the next day of oestrus, and the ovulation response, the steroid hormone levels in the serum and the immunoreactivity of tyrosine hydroxylase and dopamine β-hydroxylase in the ovaries were measured. Results In animals with the induction of polycystic ovary syndrome and β-adrenoreceptor blocking, ovulation was restored in more than half of the animals and resulted in decreased hyperandrogenism with respect to the levels observed in the estradiol valerate-treated group. Tyrosine hydroxylase and dopamine β-hydroxylase were present in the theca cells of the growing follicles and the interstitial gland. Injection of propranolol restored the tyrosine hydroxylase and ovarian dopamine β-hydroxylase levels in rats with polycystic ovary syndrome induction. Conclusions The results suggest that a single injection into the ovarian bursas of propranolol, a nonselective antagonist of β-adrenoreceptor receptors, decreases the serum testosterone concentration and the formation of ovarian cysts, improving the ovulation rate that accompanies lower levels of tyrosine hydroxylase and dopamine β-hydroxylase in the ovary.